Associations Between Traumatic Brain Injury, Suspected Psychiatric Conditions, and Unemployment in Operation Enduring Freedom/Operation Iraqi Freedom Veterans. Issue 3 (May 2016) - Pogoda, Terri K.; Stolzmann, Kelly L.; Iverson, Katherine M.; Baker, Errol; Krengel, Maxine; Lew, Henry L.; Amara, Jomana H.; Meterko, Mark
Abstract : Objective: To examine the relations among demographic characteristics, traumatic brain injury (TBI) history, suspected psychiatric conditions, current neurobehavioral health symptoms, and employment status in Veterans evaluated for TBI in the Department of Veterans Affairs. Study Design: Retrospective cross-sectional database review of comprehensive TBI evaluations documented between October 2007 and June 2009. Participants: Operation Enduring Freedom/Operation Iraqi Freedom Veterans ( n = 11 683) who completed a comprehensive TBI evaluation. Main Measures: Veterans Affairs clinicians use the comprehensive TBI evaluations to obtain information about TBI-related experiences, current neurobehavioral symptoms, and to identify suspected psychiatric conditions. Results: Approximately one-third of Veterans in this sample were unemployed, and of these, the majority were looking for work. After simultaneously adjusting for health and deployment-related variables, significant factors associated with unemployment included one or more suspected psychiatric conditions (eg, posttraumatic stress disorder, anxiety, depression), neurobehavioral symptom severity (ie, affective, cognitive, vestibular), former active duty status, injury etiology, age, lower education, and marital status. The associations of these factors with employment status varied by deployment-related TBI severity. Conclusions: Simultaneously addressing health-related, educational, and/or vocational needs may fill a critical gap for helping Veterans readjust to civilian life and achieve their academic and vocational potential.